Avaliação do desaguamento de resíduos de esgotamento de caminhão limpa-fossas através de técnica de deságue em geotêxtil e aplicação de polímeros - Paula, Edlene Sales de (2012)
The sludge from the septic tank must be removed periodically. This material has been consolidated and free fatty material is the product of anaerobic digestion transformed into simpler compounds. Are usually removed by truck clean sump and disposed in sewage treatment plants, where these exist. The sludge, despite being extremely rich in solids, has a considerable content of water which can be removed by techniques outflow. In general, it is used for dewatering to increase the solids content of the slurry reducing its volume. This material is stabilized after, for example, by composting can be applied to agricultural land as a fertilizer after treatment and assessment by testing for characterization and toxicity. Thus, the septic tank sludge disposal can have a more environmentally noble even decreases the amount of solid material in sewage treatment plants and increases the life of the ponds due to lower frequency of dredging. The purpose of this study is to develop a sludge outflow through the geotextile to evaluate the application of organic polymers and polyacrylamides through jar test and turbidity tests in order to establish the type of polymer and their concentrations which have improved efficiency reducing the solids content. The function of the polymer is to promote the aggregation of solid particles and flocculation destabilization by chemical or physical forces acting on the particles in the colloidal and suspended particulate material immersed in a liquid medium. For evaluation of geotextile tests were performed cone and bag drop. In jar tests it was found that the polymers studied have optimum turbidity removal rates (82.0% - 99.8%) applications with varying concentrations of polymer from 14 to 275mg / L. In tests of the cone removals ranged from 46.3% - 56.0%. Finally assays bag suspended removals ranged from 98.0% - 99.0%. These concentrations may change according to the characteristics of the sludge sampled.